2001
DOI: 10.1111/j.1945-5100.2001.tb01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Noble gases in enstatite chondrites I: Exposure ages, pairing, and weathering effects

Abstract: Several E chondrites yield significantly lower 38Ar ages compared to those calculated from cosmogenic 3He and 21Ne. For these E chondrites, we suggest a reduction of cosmogenic 38Ar as a result of weathering. In order to prove the possible influence of terrestrial alteration on the cosmogenic noble gas record of E-chondritic material, we simulated terrestrial weathering in an experiment of 12 weeks duration. The treatment showed that a significant amount of cosmogenic 38Ar is lost on Earth by the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 47 publications
6
49
0
Order By: Relevance
“…L chondrites in our collections have cosmic ray exposure ages of <70 Ma (Patzer and Schultz 2001). Many of these meteorites are probably derived from a body (or bodies) that formed as a rubble pile by gravitational reassembly of the fragments produced in the catastrophic disruption of a preexisting L-chondrite body.…”
Section: Origin On An L-group Parent Bodymentioning
confidence: 99%
“…L chondrites in our collections have cosmic ray exposure ages of <70 Ma (Patzer and Schultz 2001). Many of these meteorites are probably derived from a body (or bodies) that formed as a rubble pile by gravitational reassembly of the fragments produced in the catastrophic disruption of a preexisting L-chondrite body.…”
Section: Origin On An L-group Parent Bodymentioning
confidence: 99%
“…As for the case (1), cosmogenic-He/Ne data fit into the Bern plot ( Fig. 8; Eberhardt et al, 1966;Nishiizumi et al, 1980;Patzer and Schultz, 2001 21 Ne C excesses observed in small samples. For case of (2), the 21 Ne C production rate varies with target element chemistry.…”
mentioning
confidence: 54%
“…2). Heavily weathered chondrites are often more contaminated by atmospheric Kr than Xe, thus their Kr/Xe ratios are elevated from the chondritic composition (e.g., Scherer et al, 1994;Patzer and Schultz, 2001 Fig. 3 (Marti, 1967 …”
Section: Noble Gas Resultsmentioning
confidence: 99%
“…Ca and Fe concentrations play a significant role in the calculation of T 38 ages using the equation of Eugster (1988). There is also the possibility that 38 Ar was lost during weathering as pointed out for E-chondrites by Okazaki et al (2000) and Patzer and Schultz (2001). Because the Towada meteorite was found at about 10 years after falling , it could have lost part of 38 Ar during alteration on Earth.…”
Section: Cosmogenic Light Noble Gases and Cosmic-ray Exposure Agesmentioning
confidence: 99%
See 1 more Smart Citation